Interplay of Octahedral Tilts and Polar Order in BiFeO3 Films. (18th March 2013) - Kim, Young‐Min; Kumar, Amit; Hatt, Alison; Morozovska, Anna N.; Tselev, Alexander; Biegalski, Michael D.; Ivanov, Ilya; Eliseev, Eugene A.; Pennycook, Stephen J.; Rondinelli, James M.; Kalinin, Sergei V.; Borisevich, Albina Y.
<x xml:space="preserve">Abstract</x> Heterointerface stabilization of a distinct nonpolar BiFeO3 phase occurs simultaneously with changes in octahedral tilts. The resulting phase arises via suppression of polarization by a structural order parameter and can thus be identified as anti‐ferroelectric (Fe displacements – bottom panel). The phase is metastable and can be switched into a polar ferroelectric state (top panel) under an applied electric bias. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>